Implementasi Problem Based Learning Dengan Pendekatan TaRL dan CRT Untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik Pada Materi Fungsi Kelas XI-9 Di SMA Negeri 5 Medan TA 2024/2025 - Sarty Herawaty Br Sormin; Rika Kartika; Susanna Ronaria Harahap (Journal on Education, 2024)
This research aims to improve students' problem solving abilities in class XI-9 functional material at SMA Negeri 5 Medan for the 2024/2025 academic year, with a total of 36 students through Classroom Action Research (PTK). The method used is PTK with 2 cycles, where each cycle consists of 2 meetings. Each cycle is carried out with a focus on the learning model and TaRL and CRT approaches. The research results showed that there was a significant increase in learning outcomes in the second cycle compared to the first cycle. The first cycle succeeded in increasing learning preparation, interest and attitudes towards lessons, as well as student learning activities through the application of the PBL learning model and the Teaching at the Right Level (TaRL) approach. In the second cycle, improvement efforts were made by integrating the Teaching at the Right Level (TaRL) and Culturally Responsive Teaching (CRT) approaches, which resulted in consistent improvements in all aspects of observation.